HUBUNGAN TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT TERHADAP KEPEDULIAN MENJAGA KESEHATAN GIGI DAN MULUT SISWA SMPN 2 SOLOKANJERUK (Poltekkes Kemenkes Bandung, 2023)
The Maintenance of dental and oral health is one of the efforts to improve body health. One of the causes, why a person is less concerned with dental and oral health problems, is the lack of knowledge about dental and oral health. Caring is one form of real action, which is done by someone in response to a problem. Based on Lawrence Green's theory, the behavior itself is influenced by predisposing factors, which include knowledge, confidence, beliefs, and attitudes. The goal of this study is to determine the relationship between dental and oral health knowledge and concern for maintaining dental and oral health among Junior High School students 2 Solokanjeruk. The research method used analytical research with a cross-sectional approach. The population of this study amounted to 146 people. The data is processed and presented in a frequency distribution table and cross-tabulation. The results of this study showed that there was no relationship between the level of dental and oral health knowledge to concern about maintaining the dental and oral health of Junior High School students 2 Solokanjeruk.